Indicadores ecológicos no monitoramento da restauração de florestas ciliares no sul do Brasil - Piaia, Bruna Balestrin (2021)
Monitoring through good indicators is still a challenge in evaluating the results of ecological restoration. Functional diversity metrics can provide greater explanatory power to predict the success of restoration and ecosystem functioning. The general objective of this work is to evaluate ecological indicators to verify the efficiency of forest restoration in Permanent Preservation Areas in the Pampa Biome, Rio Grande do Sul. In the first study, we evaluated ecological indicators of taxonomic diversity and functional diversity of natural regeneration and planted trees to verify restoration success in three sites (Caçapava do Sul, Minas do Leão and Pantano Grande) with applied nucleation carried out seven years ago. We verify that the richness of regenerating species was similar in each area, but the richness of planted species was lower in Minas do Leão, intermediate in Caçapava do Sul and higher in Pantano Grande. There was a significant difference in the floristic composition of planted and regenerating species. The functional diversity indices were similar between planted and regenerating, with the exception of functional dispersion, although Minas do Leão presents low functional richness. This indicates that even with lower species richness and lower functional richness in planting does not imply lower species richness and flower functional richness of regenerants. The second study aimed to analyze the taxonomic and functional diversity as ecological indicators of riparian forest restoration by 14-years passive restoration, 12-years row planting and two- and seven-years applied nucleation in southern Brazil. The understory of passive restoration showed higher values for species richness, abundance, maximum height and number of individuals and species zoochoric and climax shade tolerant. The two-year applied nucleation showed the lowest values for species richness, abundance, diversity and evenness and a higher value for the number of individuals and species pioneer and anemochoric. Understory functional richness was similar between 14-years passive restoration and 12-years row planting, applied nucleation showed the lowest values and the planting ages of two and seven years did not differ statistically by the Tukey test. Functional evenness, functional divergence and functional dispersion were similar in 12-years row planting, 14-years passive restoration and seven-year applied nucleation, while two-year applied nucleation had the lowest rates. It is concluded that applied nucleation is an efficient technique for ecological restoration in the study region and favors the micro-habitat alteration and the propagules return, even with lower initial richness of planted species. Taxonomic and functional diversity indicators are efficient to demonstrate the differences in the successional trajectory time. Taxonomic and functional diversity increases with successional advancement and restoration age. Applied nucleation and passive restoration should be prioritized over row planting in landscapes with potential for natural regeneration.